EFFECTS OF POST PROCESSES ON THE MECHANICAL PROPERTIES OF TI-6AL-4V TITANIUM ALLOY BY SELECTIVE LASER MELTING - ZHANG HaiYing; DONG DengKe; SU ShaoPu; CHEN An (Jixie qiangdu)
Ti-6 Al-4 V titanium alloy specimens were built using selective laser melting. Some specimens were heat treated and some were hot-isostatically pressed. Half of these specimens in three conditions were polished. Tensile test was conducted to research into the effect of heat treatment/hot-isostatic pressing and polish on the mechanical properties. The microstructure and fractography were observed using optical microscope and scanning electron microscope to find the reason for mechanical property modifications. The test results demonstrate that,after heat treatment or hot-isostatic pressing,the ultimate tensile strength of SLM Ti-6 Al-4 V is reduced significantly while the elongation is improved by around 50%. Polish results in the increase of yield and ultimate strength by about 30 MPa for hot-isostatic pressed specimens,but leads to no apparent improvement in mechanical properties for as-built and heat treated specimens.